Invasive Heart Rate Control as a Salvage Therapy in Amiodarone-induced Thyroid Storm - Emin Evren OZCAN; Mustafa DOGDUS; Resit Yigit YILANCIOGLU; Suleyman Cem ADIYAMAN; Oguzhan Ekrem TURAN (Medeniyet Medical Journal)
Atrial fibrillation (AF) is the most common arrhythmia, and amiodarone is one of the most commonly used drugs for medical cardioversion of AF, which should be used carefully due to its toxic effects. Amiodarone-induced thyrotoxicosis (AIT) may develop in amiodarone-treated patients. In contrast, the most common rhythm disturbance accompanying a thyroid storm is AF. This association may put both AF and thyrotoxicosis treatment into a vicious circle, leading to AI cardiomyopathy. Herein, we aimed to present atrioventricular node ablation as a salvage therapy in a patient with AIT who had AF-causing hemodynamic impairment, resistance to medical therapy, and cardioversion.